Tinjauan Penggunaan Tanaman dalam Perencanaan dan Reka Bentuk Lanskap untuk Mitigasi Longsor - Utami, Ni Wayan (Jurnal Arsitektur Lansekap; Vol. 10, No. 2 Oktober 2024DO - 10.24843/JAL.2024.v10.i02.p12, 2024)
Landforms vary from flat to undulating and steep. Steepness in a landscape can enhance aesthetic value but also poses challenges if not managed properly. Landslides are a significant risk associated with steep topography, and to mitigate this impact, landscape architects can incorporate mitigation strategies within landscape planning and design. Mitigation, a biotechnological approach, has proven effective in increasing slope stability. A variety of plant strata—from groundcovers like grasses to herbs, shrubs, and trees—can be integrated into landscape plans to support landslide mitigation. This paper presents a qualitative literature review, employing descriptive-analytical methods to identify optimal criteria for plant-based landslide mitigation in landscape planning and design.